Impacto dos mecanismos da international accountability na justicialização dos direitos humanos econômicos, sociais e culturais no Brasil - Duarte Júnior, Dimas Pereira (2008)
The study of the issue of accountability has been in evidence on the political agenda worldwide, anchor itself, especially as prerequisite for the construction of representative democracies or successful poliarquies. If within the term of Political Science already acquired privileged status and features quite prepared, the same can not be said with regard to their employment at international level. His introduction in International Relations occurs with the crisis of the nation-state and with the advent of international norms protecting human rights, inserted within the United Nations from 1948 that, during the twentieth century, came to pronounce and recognize a list of rights and subject of law increasingly extensive. The purpose of this study, therefore, is to analyze the impact of mechanisms for monitoring the rights set out in the International Covenant of Economic, Social and Cultural Rights of United Nations, adopted in 1966, in the process of justiciability of these rights in Brazil from 1988, when the new constitution is promulgated saddle the restoration of the democratic system and the institutionalization of human rights and country. Assuming that the international landscape that was created after the Second War, not only recognizes the states as subjects of law is the premise of which is that the systematic part of the international accountability of economic social and cultural rights inserted within United Nations does not have sufficient sanctioning instruments for wanting the international responsibility of the State for non-compliance of obligation under the 1966 pact. However, considering the fact that the viability of the exercise of the rights set out in the pact under consideration is for the State party and not the International Organization that monitors what is shown from the analysis of the Brazilian case, is that the finalization of international accountability can be complemented by internal mechanisms, under its own legal system and constitutional homeland, mainly through the actions of the Federal Public Ministry which has at its disposal various legal instruments provided for both the Federal Constitution of 1988 as the infra-constitutional legislation